2002
DOI: 10.1023/a:1015544207121
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two orthologues of FLORICAULA/LEAFY AFL1 and AFL2 (apple FLO/LFY), were isolated from the floral buds of apple trees. Their expression was detected in various tissues and during differentiation of the floral buds. Furthermore, the flowering effectiveness of each gene was assessed with transgenic Arabidopsis. Both AFL1 and AFL2 showed high homology to each other (90%) and a high degree of similarity to PTLF and PEAFLO (70%), which are homologues of FLO/LFY from poplar and pea, respectively. RNA blot analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…It was shown that over-expression of AFL1 or AFL2 , the LFY homologs in apple, can induce the early-flowering in Arabidopsis (Wada et al, 2002). In other reports, over-expression of AtLFY in apple didn’t show the same results instead of a columnar phenotype with shorten internodes (Flachowsky et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that over-expression of AFL1 or AFL2 , the LFY homologs in apple, can induce the early-flowering in Arabidopsis (Wada et al, 2002). In other reports, over-expression of AtLFY in apple didn’t show the same results instead of a columnar phenotype with shorten internodes (Flachowsky et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Such genes are isolated from flower buds in the still initial phases of their development, from flower organs and fruits of some apple cultivars (68,110,111,118,129).…”
Section: Development Of the Flower Budsmentioning
confidence: 99%
“…Although there are fundamental differences in the flowering process between annual and perennial plants, the genetics of FI and floral organ formation are likely to be similar among these plants (Tan and Swain, 2006). A set of apple genes with sequence similarity to genes involved in floral meristem transition of Arabidopsis has been identified and subjected to expression studies (Jeong et al , 1999; Sung et al , 1999; Kotoda et al , 2000, 2002, 2003, 2006, 2010; Van der Linden et al , 2002; Wada et al , 2002; Kotoda and Wada, 2005; Esumi et al , 2005). Overexpression of the apple gene orthologues of LFY , AFL1 , and AFL2 ( APPLE FLORICAULA/LFY ) (Wada et al , 2002), as well as MdMADS2 and MdMADS5 , orthologues of the Arabidopsis FRUITFULL ( FUL ) and AP1 , resulted in early flowering in heterologous systems (Sung et al , 1999; Kotoda et al , 2002).…”
Section: Introductionmentioning
confidence: 99%